Robust governance in turbulent times - Ansell, Christopher K., 1957- (Cambridge University Press, 2024)
This Element aims to build, promote, and consolidate a new social science research agenda by defining and exploring the concepts of turbulence and robustness, and subsequently demonstrating the need for robust governance in turbulent times. Turbulence refers to the unpredictable dynamics that public governance is currently facing in the wake of the financial crisis, the refugee crisis, the COVID-19 pandemic, the inflation crisis etc. The heightened societal turbulence calls for robust governance aiming to maintain core functions, goals and values by means of flexibly adapting and proactively innovating the modus operandi of the public sector. This Element identifies a broad repertoire of robustness strategies that public governors may use and combine to respond robustly to turbulence. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 30 Apr 2024).
Keywords: Political science.; Political planning.; Public administration.